Diuretic activity of the bark of Eysenhardtia polystachya (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to evaluate the diuretic activity of Eysenhardtia polystachya bark aqueous extract at different doses in a rat model. Different doses of E. polystachya (125, 250, 500 and 750 mg/kg body weight), furosemide (4 mg/kg) and vehicle were administered per os to female rats (n=6 animals per group). After 6 hours in metabolic cages, the effect on urinary flow, glomerular ?ltration rate and electrolyte balance of sodium and potassium were assessed in all animals. E. polystachya at the doses of 500 and 750 mg/kg induced diuretic activity, since markedly increased (p